Multicenter Evaluation of Time, Operational, and Economic Efficiencies of a New Preloaded Intraocular Lens Delivery System versus Manual Intraocular Lens Delivery - Mendicute J (Dove Medical Press, 2021)
Javier Mendicute,1 Lucia Bascarán,1 Luis Pablo,2 Cédric Schweitzer,3 Laurent Velasque,4 Christine Bouchet,5 Aldo A Martinez5 1Department of Ophthalmology, Hospital Universitario Donostia, San Sebastián, Spain; 2Department of Ophthalmology, Hospital Universitario Miguel Servet, Zaragoza, Spain; 3Department of Ophthalmology, Bordeaux University Hospital, Bordeaux, France; 4Centre Retine Gallien, Bordeaux, France; 5Alcon Research LLC, Fort Worth, TX, USACorrespondence: Javier MendicuteDepartment of Ophthalmology, Hospital Universitario Donostia, Paseo Dr. Beguiristáin, 115, San Sebastián, 20014, SpainTel +34-943322233Email mendicutejavier@gmail.comPurpose: To evaluate intraoperative intraocular lens (IOL) delivery time and total surgical case time using the UltraSert preloaded delivery system (System U) during routine cataract surgeries and to compare with the manually loaded Monarch delivery system (System M). Physician satisfaction with System U was also assessed.Patients and Methods: In this prospective observational study, subjects ≥ 18 years old underwent cataract surgery in 1 eye and received the AcrySof IQ IOL via the manually loaded System M (n=103) or the AcrySof IQ IOL model AU00T0 via the preloaded System U (n=93). Procedures were digitally recorded by an external camera or by a camera within the operating microscope. Device preparation, IOL delivery, and IOL positioning times were evaluated by 2 independent graders. Pearson χ2 test or Fisher exact test was used for categorical variables and Student’s t-test or Wilcoxon rank-sum test for continuous variables (all tests were 2-sided and performed at a 5% α-level). Physician satisfaction levels were assessed using questionnaires.Results: Lens delivery time was similar for System U and System M (12.9± 5.1 and 12.2± 6.3 s; P=0.412). Mean device preparation time for System U was significantly shorter compared with System M (30.3± 6.6 versus 59.8± 31.0 s; P< 0.05). This resulted in a significantly shorter total intraoperative time (device preparation + lens delivery) with System U versus System M (43.0± 8.6 versus 72.0± 32.5 s; P< 0.05). Total surgical case time (device preparation + lens delivery + lens positioning and unfolding) was shorter for System U versus System M (56.6± 12.6 versus 89.6± 34.6 s; P< 0.05). Physicians reported greater satisfaction levels with System U compared with other devices.Conclusion: Use of the preloaded delivery system (System U) resulted in faster device preparation and reduced total surgical time compared with the manually loaded system (System M). System U was intuitive to use, and physicians preferred it to other devices.Keywords: cataract surgery, intraocular lens delivery time, Monarch, UltraSert